MANUFACTURING PROCESSES MODELING OF INDUSTRIAL ENTERPRISES BY MEANS OF ARENA SYSTEM SIMULATION - Vysochina, O. S.; Danich, V. N.; Parhomenko, V. P. (Radio Electronics, Computer Science, Control, 2012)
The article presents a manufacturing processes simulation model of industrial car valves production enterprises. A description of the model building and simulation results were considered.